Work Related Ocular Injury: Nepal - Limbu, Ben; Moore, Grant; Marvasti, Amir H.; Poole, Mariel E.; Saiju, Rohit (Nepalese Journal of Ophthalmology, 2018)
Introduction: Occupational eye injuries comprise a major source of ocular trauma. Knowledge of the epidemiology of occupational eye injuries is essential to formulate viable safety strategies. Objectives: To evaluate the demographics, patterns of protective eye wear use, and patterns of occupational eye injury among workers in Hetauda, Nepal. Materials and methods: Community based cross-sectional prospective survey was carried out from September 2010 to July 2011. Survey included all workers irrespective of their age and those who are willing to participate in survey by filling details on structured questioners and comprehensive eye examination at community level. Results: 1236 surveys were collected. 38.3% (473) of workers surveyed reported experiencing a work-related eye injury. Over two-thirds [68.3% (844)] of workers surveyed reported never wearing safety eyewear while at work. There was a positive correlation between male sex (P<0.001), reported previous work-related injury (P<0.001), and attending school (P=0.016) and use of personal protective equipment (PPE). Conclusions: The population studied demonstrates a significant level of work related injury. There are potentially modifiable factors that could lead to increased use of eye protection.